(untitled) (Biological Sciences - PJSIR, 2023)
Laboratory studies were conducted to determine the effect of low temperatures and gamma radiation on parasitization of Cotesia flavipes (Cameron) on Chilo infuscatellus (Snellen). Five temperatures groups i.e., 5.0, 7.5, 10.0, 12.5 and 15.0 °C along with control (25±1 °C) were maintained in separate incubators as ten larvae of 3rd, 4th and 5th instar C. infuscatellus were provided to coupled C. flavipes for parasitization. Cobalt-60 Telegraphy machine was used for gamma radiations of 20, 40, 60, 80 and 100Gy to fifty larvae of 3rd, 4th and 5th C. infuscatellus instars parasitized with C. flavipes. Results regarding number of C. flavipes cocoons, adult emergence, sex ratio and adult longevity indicated a declined trend with lowering temperatures as maximum parasitoid performance was recorded at control. Moreover, 75Gy was found more effective to support parasitization and development of C. flavipes and its preferred 5th instar C. infuscatellus larvae than 3rd and 4th instars. Therefore, 75Gy irradiated 5th instar C. infuscatellus larvae should be used for the laboratory rearing of C. flavipes at 25±1 °C.